2014
DOI: 10.1002/jsfa.6790
|View full text |Cite
|
Sign up to set email alerts
|

Effect of nitrogen fertilisation and irrigation on phenolic content, phenolic acid composition, and antioxidant activity of winter wheat grain

Abstract: An appropriate irrigation and N management improved antioxidant content and AOA in wheat grain. Generally, I1 N240 and I1 N300 treatment resulted in the higher TPC, TFC, AOA, as well as phenolic acid, i.e. FA and VA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
42
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(52 citation statements)
references
References 29 publications
9
42
1
Order By: Relevance
“…The results obtained in the present study are in opposition to the one cited above. However, in our research, control was N deficient, while in research of Ma et al (2015) they are most likely in optimum and higher than in optimum. It also may be speculated that the increased biosynthesis (accumulation) of phenolics (cross-talk response to stress conditions) was caused by the induction of the plants' natural resistance by some components present in SL, especially Cd 2+ and Pb 2+ (Michalak 2006, Lin et al 2007).…”
Section: Discussioncontrasting
confidence: 60%
See 1 more Smart Citation
“…The results obtained in the present study are in opposition to the one cited above. However, in our research, control was N deficient, while in research of Ma et al (2015) they are most likely in optimum and higher than in optimum. It also may be speculated that the increased biosynthesis (accumulation) of phenolics (cross-talk response to stress conditions) was caused by the induction of the plants' natural resistance by some components present in SL, especially Cd 2+ and Pb 2+ (Michalak 2006, Lin et al 2007).…”
Section: Discussioncontrasting
confidence: 60%
“…According to the literature, accessibility of nitrogen to plants is important due to effects on the antioxidant potential. The results of Ma et al (2015) showed that fertilization with nitrogen (180 and 240 kg N ha ) decreased the antioxidant activity of winter wheat when compared to non-fertilized cultivation. The results obtained in the present study are in opposition to the one cited above.…”
Section: Discussionmentioning
confidence: 98%
“…The means of the TPC values for soluble compounds ranged between 0.06 and 0.12 mg GAE g −1 DM. In contrast, Ma et al () reported tenfold higher TPC values for soluble compounds, as well as increasing TPC and ferulic acid concentrations due to higher amounts of N fertilizer. These differences could be explained by much higher dosages of N fertilizer (up to 300 kg N ha −1 ) which have been used in the study of Ma et al.…”
Section: Discussionmentioning
confidence: 89%
“…In wheat (Triticum aestivum, Poaceae), there is recording of the rising of phenolic acids by increasing the N (Ma et al, 2015). In crabgrass (Digitaria sanguinalis, Poaceae), the increase of N incremented the concentration of these acids (Chou and Lee, 1988).…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, there is no clarity about its effect on the allelopathic activity and on the concentration of allelochemicals. Some authors mention the increase of secondary metabolites under low N availability in the soil (Ibrahim et al, 2011), while others indicate that N increases the concentration of phenolic acids (Chou and Lee, 1988;Ma et al, 2015). Phenolic compounds may, in turn, be in a higher or a lower concentration, depending on the physiological age of the plants.…”
Section: Introductionmentioning
confidence: 99%